PENGETAHUAN MAHASISWA AKPER HERMINA MANGGALA HUSADA TENTANG COVID-19 DAN CARA PENCEGAHANNYA - Retno Winarti, Suryani Hartati (JURNAL ILMIAH KEPERAWATAN ALTRUISTIK)
Covid  19 is an infectious disease currently being faced by the world. Good knowledge on Covid 19 contributes in preventing Covid 19. The purpose of this study is to find out the knowledge of nursing student about Covid 19 and how to prevent it. This cross-sectional study used consecutive sampling technique with 110 respondents as student of Hermina Manggala Husada Nursing Academic. The survey was conducted using a questionnaire consisting of 20 question items about Covid 19 and how to prevent it. The knowledge of nursing  students was measured using a guttmen scale with a cut of point 17. Data analysis was carried out using ci square. The results showed that most of the students had good knowledge about covid 19 (56.4%), but there were still 43.6% students who did not have good knowledge about covid 19, most students got information about covid 19 from Television and online media. Good knowledge is the basis for preventing Covid 19, so it is important to make Covid 19 a teaching material in class so that all students have good knowledge about Covid 19.    Keywords : Covid 19 , Student’s Knowledge